Developing novel anthelmintics from plant cysteine proteinases - Behnke, Jerzy M.; Buttle, David J.; Stepek, Gillian; Lowe, Ann; Duce, I.R. (BioMed Central, 2008)
Intestinal helminth infections of livestock and humans are predominantly controlled by treatment with three classes of synthetic drugs, but some livestock nematodes have now developed resistance to all three classes and there are signs that human hookworms are becoming less responsive to the two classes (benzimidazoles and the nicotinic acetylcholine agonists) that are licensed for treatment of humans. New anthelmintics are urgently needed, and whilst development of new synthetic drugs is ongoing, it is slow and there are no signs yet that novel compounds operating through different modes of action, will be available on the market in the current decade. The development of naturally-occurring compounds as medicines for human use and for treatment of animals is fraught with problems. In this paper we review the current status of cysteine proteinases from fruits and protective plant latices as novel anthelmintics, we consider some of the problems inherent in taking laboratory findings and those derived from folk-medicine to the market and we suggest that there is a wealth of new compounds still to be discovered that could be harvested to benefit humans and livestock.